Diagnosing collective action in Small-Scale Fisheries for the establishment and management of Marine Areas of Responsible Fishing (AMPR) in the Gulf of Nicoya, Costa Rica - Chávez Carrillo, Isis I. (2018)
Tesis (maestría) - CATIE, Turrialba (Costa Rica), 2018